A Study of Effects of Social Factors on Parents, Participation in Hamadan Senior High Schools - alimohammad ghodsi; esmaeil balali; neda latifipak (توسعه اجتماعی)
The schools mission as an educational institution is education and training. It’s not possible doing this mission without the participation of parents. In this regard, this study considers parent participation as a social practice. General purpose of this study is to identify status of parent participation, and examination of effective social factor on it. Sample of this study is 250 students’s which were selected from among 12820 of girls senior high schools student parent who were in the academic year (2014-2015). It has performed with measurement. Parents, participation in 6 dimensions, social affairs, training affairs, communication between home and schools, educational affairs, communication with staff and student and financial affairs. Variable is institution trust, social and economic status, stereotype, powerlessness, self efficacy, personal attitude. There is direct and significant correlation between institution trust, self efficacy, personal attitude and parent participation. There is reversed and significant correlation between powerlessness and parent participation and there is not significant relationship between social and economic status, stereotype and parent participation. Based result of this study, above variable institution trust and self efficacy have 6 variance of parent participation. The lowest rate of parent participation in the field of financial and maximum amount is in education affairs.